Introduction to the Special Issue on Early Care and Education Professionals' Social and Emotional Well-being. Issue 7 (2nd October 2020) - Jennings, Patricia A.; Jeon, Lieny; Roberts, Amy M.
ABSTRACT: Early care and education (ECE) professionals' social and emotional well-being has emerged as an area of focus for improving program quality. ECE professionals are experiencing increasing levels of stress and burnout, which is threatening the quality of early childhood education and care. This article introduces the special issue devoted to understanding early childhood professionals' social and emotional competence and well-being and their relationship to program quality and child outcomes. The purposes of this special issue are to (a) describe the nature of ECE professionals' social and emotional competence and well-being, (b) understand the factors that contribute to ECE professionals' social and emotional competence and well-being, (c) understand to what extent and how ECE professionals' social and emotional competence and well-being impacts classroom quality as well as children's developmental outcomes, and (d) present evidence-based approaches that support ECE professionals' social and emotional competence and well-being. For the purposes of this issue, ECE professionals include early childhood educators (e.g., teachers or home-based child care providers), practitioners (e.g., home visitors, mental health consultants, specialists, etc.) and early childhood leaders (e.g., directors, principals, or administrators) who serve children from birth to third grade. In this introductory article we conclude with a discussion of implications of this research for future research, policy, and practice.